A study of the extent of application of information technology among government agency libraries in Metro Manila - Samonte, Marc Raymond J. (Institute of Library and Information Science, University of the Philippines Diliman, 2003)
This study primarily aims to determine the proficiency of government agency libraries in terms of their utilization of information technology. It seeks to ascertain existing information technology applications and intends to compare and establish which among these libraries are at the forefront with regards to the prevalence of technological resources. The evaluation of information technology was conducted with primary considerations of audiovisual resources, as well as elements of computer-and-communications systems. The population of the study consists of the central/main libraries of Philippine government agencies in Metro Manila. Questionnaires were uses as data gathering tools, with descriptive statistics including frequency distribution tables, graphs and charts were employed to analyze and represent results. The chi-square (X) test was used for inferential statistics.